Development of a Multiplex RT-PCR for the Simultaneous Detection of Five Viruses and Viroids in Peach - Jeong-Eun Kim; Boram Kwon; Eun Jung Heo; Eunhae Baek; Gahyun Son; Hyun Joo Shin (Research in Plant Disease)
A multiplex reverse transcription-polymerase chain reaction (mRT-PCR) assay was developed for the simultaneous detection of three viruses and two viroids infecting peach trees, including apple chlorotic leaf spot virus, plum bark necrosis stem pitting-associated virus, peach-associated luteovirus, peach latent mosaic viroid, and hop stunt viroid, which have been reported in peach trees in Korea. Species-specific primers were designed, optimized, and integrated into a single primer set to ensure high sensitivity and specificity. Detection limits of the primers were assessed using serial dilution of total RNA under both single and multiplex conditions. The mRT-PCR assay was subsequently applied to 175 peach samples from 80 cultivars collected in the Gyeongbuk region, successfully identifying viral infections across a diverse range of peach varieties. This mRT-PCR assay is rapid, sensitive, and scalable diagnostic tool that allows for the simultaneous detection of multiple viruses and viroids, offering significant advantages over conventional methods. Its suitability for large-scale prevalence surveys and epidemiological studies, as well as its effectiveness in producing disease-free seedlings, makes it particularly valuable for managing peach-infecting viruses and viroids.